New research on ternary hybrid nanofluid flow across a surface with the influence of thermal radiation using semi-numerical simulation - Rehman, Ali; İnç, Mustafa; Sudarmozhi, Krishna (De Gruyter Poland Sp Z O O, 2026)
The present study presents a semi-numerical simulation to investigate the flow behaviour and energy transfer of a ternary hybrid nanofluid (THNF) over a stretching surface, accounting for viscous dispersion and thermal radiation. To improve its thermal and rheological performance, the model combines curvature, couple stress, and higher thermal conductivity. This is achieved by suspending three different nanoparticles - Alumina oxide, Ag,TiO2,Al2O3 in a blood non-Newtonian base fluid. The authors reduce the controlling partial differential equation to a system of nonlinear ordinary differential equation via similarity transformations. After that, semi-numerical solutions are obtained using the homotopy analysis method, which provides flexibility in controlling convergence. The impact of several significant parameters on the velocity and energy fields is thoroughly examined, including the couple-stress parameter, nanoparticle volume fractions, radiation, curvature parameter, magneto-hydrodynamics parameter, and Eckert number. The results show that, while pair stress effects tend to lower flow resistance, the addition of ternary hybrid nanoparticles significantly improves heat transfer performance compared to traditional nanofluids. It is also discovered that the thickness of the thermal boundary layer is influenced by the surface's curvature. These results provide new insights into optimising energy transfer processes in advanced thermal systems using tailored nanofluids.
Keywords: curved stretching surface; Ag,TiO2,Al2O3; homotopy analysis method (HAM); ternary hybrid nanofluid